Etnomatematika pada Batik Lukis Daun Singkong di Rumah Produksi Daweea Batik Bondowoso - Erfan Yudianto; Susanto Susanto; Sinta Priciliya (Universitas Hamzanwadi, 2020)
Ethnomathematics is the relationship between culture and mathematics found in society's habits, where people have unconsciously applied mathematical concepts in their culture or habits. The custom referred to in this study is what is done by batik in making one batik sheet every time. The purpose of this study was to describe ethnomathematics on cassava leaves in the production house Daweea Batik Bondowoso East Java. This research is qualitative research with an ethnographic approach. The subject of this study was the craftsmen in the Daweea Bondowoso Batik production house. Data collection methods used are observation, interviews, and documentation. The observation was carried out by the researcher himself and assisted by two observers who were provided with observation guidelines. Interviews were conducted to artisans in Daweea Bondowoso batik production house, while the documentation was carried out by the researcher himself using a camera recorder. The results of this study indicate the existence of ethnomathematics in cassava leaves batik painting. Geometry concepts or elements found include points, lines, angles, flat shapes (rectangles, squares), congruence, concordance, equations, and geometric transformations (dilation).